INDETIFYING INTERPERSONAL MEANING IN EFL TEXTBOOK “ENGLISH FOR NUSANTARA” FOR SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Ramadhani, Adinda Nuril; Samsi, Yogi Setia; Utami, Praditya Putri (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This study focuses on identifying interpersonal meaning in the EFL textbook entitled English For Nusantara issued by the Ministry of Education and Culture Indonesia. This study has two objectives, the first is to analyze the types of mood structures contained in the textbook and the second is to categorize the most dominant type of mood in the textbook. This research uses a qualitative method. The data also was taken from the conversations, worksheets, etc contained in each chapter. From the results of the research, there are four types of mood types found in the textbook consisting of declarative, interrogative, imperative, and exclamative mood. The most dominant type of mood in the textbook is declarative and the least frequent is exclamative. The results show that the 342 clauses in the text are dominated by declarative sentences, followed by 222 clauses of interrogative sentences. The imperative is 49 clauses and the exclamative, which appears much less frequently, appears around 17 clauses. The function of the speech contained in the EFL textbook